Das Problem der Gewannfluren in südwestdeutscher Sicht - Huttenlocher, Friedrich (ERDKUNDE, 1963)
The first part of this paper reports in chronological order about the most important stages of research into the origin of field patterns in southern Germany. Gradmann's Gewanndorf (furlong village) is discussed in detail since by means of the style of the field pattern he had grasped the genetic position and possibilities of development of a settlement type; he had thus pointed the way towards a regional interpretation of settlement types. His Gewanndörfer, as Schroder has shown, are merely a variant of the Gewannflurdorfer (open field villages) i. e. those where the strips are very narrow. Their occurrence is confined to the Rhenish areas where divided inheritance prevails. The eastern boundary towards the areas of prevailing undivided inheritance and broad field strips is recognized as an important cultural boundary of great age. The very active recent research work concerned with field patterns carried out in Franconia and Bavaria, which mainly uses a genetic approach, is particularly concerned with the question of whether Gewanne (furlongs) or Flurblöcke (consolidated blockfields) were characteristic of the original core of the plough land. Investigations over extensive areas by Krenzlin and others have shown that in northern Franconia block shaped fields were in many cases characteristic of the original cores of the arable; in the areas of early settlement of south-west Germany block shapes and genuine furlongs are as a rule juxtaposed. The paper then discusses in detail the open fields which originated from planned regular broad strips since these types frequently occur over extensive areas quite exclusively, as for instance in the Alpine Foreland, the Rhön foreland (Krenzlin) and the Upper Rhine valley. Those of the western upper Rhine are long Wegedorfer (path villages) whose plough land is divided into long parallel strips. Nitz was able to illustrate convincingly that these were early instances of planned foundations for free Wehrbauern (soldier-peasants) only subject to the king, established by the Frankish estate administration. Nitz was also able to prove the further development of these well thought out land allocations to the Waldhufen (consolidated farms of rectangular shape, lying alongside each other) already in the 9th century in the Odenwald possessions of the Imperial Abbey Lorsch. In the second part of the paper the author relates and evaluates the results of a work by Jänichen, a historian. He established on the basis of early Urbare (manorial rolls) of Western Swabia that there the original ridge and furrow cultivation was early displaced by slightly raised bed cultivation (Beetbau) and this in turn, already in the 13th century, by flat cultivation (Ebenfeldbau). He also showed that simultaneously with this intensification a change occur red from a ploughland consisting of isolated pieces of arable to continuous arable land by utilizing the balks and grass covered access paths. The eastern boundary of this region of early flat cultivation coincides very largely with that of the open fields with narrow strips and custom of divided in heritance. It separates the western areas of large villages with a tendency towards cottage industry from the eastern purely farming country. The ultimate cause of this early development of the western areas lies according to Jänichen in the fact that there the demesne farms with their serf labour were absorbed by the villages early and with their entire land, and this brought about the introduction of emphasized grain growing on regularly, not intermittently, cultivated fields. The development of the farm land of the old villages of south-west Germany is thus composed of a number of phases: the period of the demesne farms (villicationes) of the early Middle Ages, the period of planned foundations with their large block fields of the terra salica and the fur longs of the holdings subject to work on the former, the period of an agricultural climax during the height of the Middle Ages with the formation of the social organization of the open field village, the disappearance of the demesne farms, and the change over to continuous arable land and flat cultivation. This is followed by an expansion of the arable on to marginal land of deserted settlements during the late Middle Ages and at last of sharing out of the commons owing to the change over to stall feeding. The main characteristics of this development are the continuous widening of the class of people with rights of land use and the early levelling of the social structure. This development did not take place in the areas with undivided inheritance in eastern Swabia. Taking examples from the Ulm Alb, which was investigated in detail by Grees, it is shown that there the cottagers, etc., were only able to obtain very modest shares and rights. The object of this paper is to show that in the south-west German cultural province, in the area of Gradmann's Gewanndorfer, the open fields consist of many different components, that they have arisen from large block fields later divided into strips, furlongs where strips were allocated from the beginning to different land holders, and furlongs which resulted from the sharing out of land amongst the village community; it is to show further in which way the development of farm land division is an indicator of social structure and thus provides substantial cultural geographical information for the various cultural provinces.